Coloniality and decolonial pedagogy: To think of other education - Catherine Walsh; Luiz Fernandes de Oliveira; Vera Maria Candau (Arizona State University, 2018)
This paper aims to present the special issue on Coloniality and Decolonial pedagogy. The work presents and discusses the theoretical perspectives on Modernity / Coloniality and its main concepts, particularly the modernity, the coloniality and decolonial pedagogy concepts. We also develop the debate about coloniality and decolonial pedagogy in this dossier, highlighting that this theoretical perspective is built in a dialogue with several educational realities and with social movements.